ENVIRONMENTAL MANAGEMENT AND MONITORING EFFORTS (UKL-UPL) FOR OIL AND GAS SECTOR - R. Desrina (Testing Center for Oil and Gas LEMIGAS, 2005)
Environmental monitoring is an integrated activity of the environmental management in general. Normally, any activity or industry has a written environmental management program called Environmental Management Plan or Rencana Pengelolaan Lingkungan (RKL). This document that has to be legalized or approved by the government describes an environmental management program that shall be implemented by the industry following the establishment of a project. Eventually, success of the RKL implementation can be monitored through environmental monitoring program that has been described in a document defined as Environmental Monitoring Plan or Rencana Pemantauan Lingkungan (RPL). Both RKL and RPL are the environmental management system planning documents that are established following the environmental impact assessment (EIA) AMDAL (Analisis Mengenai Dampak Lingkungan) study for a new project. Regulation regarding with the compulsory for conducting AMDAL is defined in the Government Regulation (Peraturan Pemerintah, PP) No. 29/1986, which is then revised by PP No. 51/1993, and finally by PP. No. 27/1999. Many questions are launched by the oil and gas industries in Indonesia, since these industries have been started their activity long before the AMDAL regulation being put into effect. Moreover, the recent ministerial decree